Interactions of donor sources and media influence the histo‐morphological quality of full‐thickness skin models. Issue 10 (19th September 2016) - Lange, Julia; Weil, Frederik; Riegler, Christoph; Groeber, Florian; Rebhan, Silke; Kurdyn, Szymon; Alb, Miriam; Kneitz, Hermann; Gelbrich, Götz; Walles, Heike; Mielke, Stephan
Abstract: Human artificial skin models are increasingly employed as non‐animal test platforms for research and medical purposes. However, the overall histopathological quality of such models may vary significantly. Therefore, the effects of manufacturing protocols and donor sources on the quality of skin models built‐up from fibroblasts and keratinocytes derived from juvenile foreskins is studied. Histo‐morphological parameters such as epidermal thickness, number of epidermal cell layers, dermal thickness, dermo‐epidermal adhesion and absence of cellular nuclei in the corneal layer are obtained and scored accordingly. In total, 144 full‐thickness skin models derived from 16 different donors, built‐up in triplicates using three different culture conditions were successfully generated. In univariate analysis both media and donor age affected the quality of skin models significantly. Both parameters remained statistically significant in multivariate analyses. Performing general linear model analyses we could show that individual medium‐donor‐interactions influence the quality. These observations suggest that the optimal choice of media may differ from donor to donor and coincides with findings where significant inter‐individual variations of growth rates in keratinocytes and fibroblasts have been described. Thus, the consideration of individual medium‐donor‐interactions may improve the overall quality of human organ models thereby forming a reproducible test platform for sophisticated clinical research. Abstract : The overall histopathological quality of human artificial skin models may vary significantly. Therefore, the effects of manufacturing protocols and donor sources on the quality of skin models is studied. It is found that both media and donor age affect the quality of skin models significantly in univariate as well as multivariate analyses. Consequently, the consideration of individual medium‐donor‐interactions may improve the overall quality of human organ models as reproducible test platforms for sophisticated clinical research.